Elevating Consumer Decision Journey to Increase Consumer Loyalty in Tokopedia and Shopee for PT. SNACK LEZAT Products - Mulya, Ardyanto; Wibowo, Satya Aditya; Purwanegara, Mustika Sufiati (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. Southeast Asia region's digital service growth trend is accelerating, with 60% of new digital users joining in the previous two years. This has an effect on e-commerce sales, which have risen quickly in recent years and are expected to rise further. Edible groceries in Indonesia are expected to increase with compounded annual growth rate 16.9% between 2022 - 2027. This growth is in line with the retail evolution from traditional market, modern market, to digital market PT. SNACK LEZAT is a global snack company and currently is focusing on e-commerce channels that still in an early stage of development and the sales are largely dependent on promotional periods. This research aims to identify the stages of the consumer decision journey to loyalty, so the right marketing strategy can be formulated and increase the repeat buyers to create a higher and sustained sales baseline. This research methodology was carried out using qualitative in-depth interviews and netnography. In-depth interviews were conducted with eight respondents, four of whom had purchased PT. SNACK LEZAT and four of whom had never purchased PT. SNACK LEZAT product. Netnography is carried out using the word cloud analysis based on product reviews in Shopee and Tokopedia platforms. The findings of this study reveal the expectations of each stage in consumer decisions journey to determine purchases on e-commerce platforms.